2012
DOI: 10.1007/s00005-012-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Matched Sibling Versus Matched Unrelated Allogeneic Hematopoietic Stem Cell Transplantation in Children with Severe Acquired Aplastic Anemia: Experience of the Polish Pediatric Group for Hematopoietic Stem Cell Transplantation

Abstract: In the study, 48 children with severe acquired aplastic anemia (SAA) transplanted from matched sibling donor (MSD) between 1991 and 2009, and 38 children with SAA transplanted from matched unrelated donor (MUD) between 2000 and 2009 were evaluated. Engraftment was achieved in 45 (93.75 %) patients after MSD-hematopoietic stem cell transplantation (HSCT) and in 33 (86.8 %) after MUD-HSCT. Transplant-related mortality rate after MSD-HSCT was 8 %, while 37 % after MUD-HSCT. After MSD-HSCT 44 (91.7 %) patients are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…1720 Previous studies suggest that optimal donor selection is a key parameter for improving survival in those patients. 21,22 In our study, longer donor leukocyte telomere length was associated with a higher overall survival probability in severe aplastic anemia patients who underwent allogeneic unrelated HCT (5-year OS=56% vs. 40%, in the long vs. short donor leukocyte telomere length group, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…1720 Previous studies suggest that optimal donor selection is a key parameter for improving survival in those patients. 21,22 In our study, longer donor leukocyte telomere length was associated with a higher overall survival probability in severe aplastic anemia patients who underwent allogeneic unrelated HCT (5-year OS=56% vs. 40%, in the long vs. short donor leukocyte telomere length group, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who lack a matched sibling donor or those older than 40 years typically receive at least 1 round of immunosuppression therapy before considering alternative donor HCT [4]. Despite advances in HLA-typing techniques and therapeutic strategies for HCT, long-term survival after unrelated donor HCT for SAA is still unsatisfactory [5-8]. Recipient age, stem cell source, and time between SAA diagnosis and HCT are the strongest risk factors for poor survival in both matched sibling and unrelated donor HCT for SAA [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Graft failure represents an important complication of BMT in patients with SAA. In our study, primary graft failure was observed in five patients, all of whom undergoing BMT from a URD, as previously reported . Eleven additional patients had secondary graft failure.…”
Section: Discussionmentioning
confidence: 95%